Disrupting Flavone Synthase II Alters Lignin and Improves Biomass Digestibility . Issue 2 (6th April 2017) - Lam, Pui Ying; Tobimatsu, Yuki; Takeda, Yuri; Suzuki, Shiro; Yamamura, Masaomi; Umezawa, Toshiaki; Lo, Clive
Abstract : Disruption of the flavone synthase II gene in rice results in an altered cell wall lignin incorporating naringenin as a novel flavonoid component and improves biomass saccharification efficiency. Abstract: Lignin, a ubiquitous phenylpropanoid polymer in vascular plant cell walls, is derived primarily from oxidative couplings of monolignols ( p -hydroxycinnamyl alcohols). It was discovered recently that a wide range of grasses, including cereals, utilize a member of the flavonoids, tricin (3′, 5′-dimethoxyflavone), as a natural comonomer with monolignols for cell wall lignification. Previously, we established that cytochrome P450 93G1 is a flavone synthase II (OsFNSII) indispensable for the biosynthesis of soluble tricin-derived metabolites in rice ( Oryza sativa ). Here, our tricin-deficient fnsII mutant was analyzed further with an emphasis on its cell wall structure and properties. The mutant is similar in growth to wild-type control plants with normal vascular morphology. Chemical and nuclear magnetic resonance structural analyses demonstrated that the mutant lignin is completely devoid of tricin, indicating that FNSII activity is essential for the deposition of tricin-bound lignin in rice cell walls. The mutant also showed substantially reduced lignin content with decreased syringyl/guaiacyl lignin unit composition. Interestingly, the loss of tricin in the mutant lignin appears to be partially compensated by incorporating naringenin, which is a preferred substrate of OsFNSII. The fnsII mutant was further revealed to have enhanced enzymatic saccharification efficiency, suggesting that the cell wall recalcitrance of grass biomass may be reduced through the manipulation of the flavonoid monomer supply for lignification.